PENGGUNAAN PROSEDUR REGULA-FALSI DAN INTERVAL BAGI DUA UNTUK PENCARIAN AKAR PADA FUNGSI POLINOMIAL BERDERAJAT TIGA - Moh Rofi; Nur Hafid; Adhi Priyanto (LPPM Politeknik Saint Paul Sorong, 2023)
Finding the root of a function cannot always be solved analytically, namely an equation of a non-linear function, so it must be done numerically with the help of a computer to perform computations, using a certain programming language. transcendental function equations and polynomial function equations. In the Non Linear Equation System, among several solution Procedures that are often used are the Newton-Raphson, the Secant, the Bisection (Dividing Interval), the False-Regulatory Procedure. In this case, the authors interested to analyzing two existing Procedures in finding the root of a non-linear function in the form of a three-degree polynomial function. This process of analysis uses the Java of programming language tool, with the reason to make it easier in terms of the algorithm analysis of completion of Procedure, and to make it easier in monitoring in terms of execution time and analysis of the output results. Recording to that reasion, we can clearly know what the differences are between the False-Position Procedure and Interval Bisection Procedure.